Equity mutual fund performance Risk factors - Akhmadi Akhmadi; Fauji Sanusi; Dony Dony (Jurnal Riset Akuntansi Terpadu, 2023)
This study aimed to look at the factors influencing both traditional and Islamic equities fund performance while analyzing stock fund performance. The population of the study consisted of 300 conventional and sharia mutual funds registered with and disclosed by the Financial Services Authority for the years 2014 to 2018. Additionally, 100 people were selected as the research sample by the purposive technique. Data analysis employed both descriptive and inferential statistics, including multiple regressions, conventional assumption tests, and hypothesis testing. The results of the study show that the performance of conventional stock mutual funds is significantly influenced by conventional stocks, stock selection, market timing, and fund size.Cash flow and fund longevity, however, made no appreciable difference. In contrast, the size and durability of the fund have a significant impact on the performance of sharia mutual funds in the stock market. Meanwhile, there is no noticeable impact from market timing or fund cash flow. This research has several limitations because it was only conducted on the Indonesian capital market and did not account for any potential strengthening or weakening variables. Future research should concentrate on these elements.